GENOTYPE x ENVIRONMENT INTERACTION ANALYSIS FOR TUBER YIELD OF POTATO USING A GGE BIPLOT METHOD IN AMHARA REGION, ETHIOPIA - Gedif, M; Yigzaw, D (Potato Journal, 2014)
Potato is one of the important crops grown in mid and high altitude areas of Ethiopia. Several potato genotypes have been introduced in different parts of this region. However, the stability and performance of these genotypes is not yet assessed. Therefore, a study to determine the effect of genotype, environment and their interaction for tuber yield and identify stable potato genotypes was conducted using eight potato genotypes in rainfed production season of years 2010 and 2011 at five potato growing locations in the region. Among the testing locations, the superior mean tuber yield (25.43 t/ha) was obtained at Adet while the inferior (13.89 t/ha) was at Injibara. Similarly, among the genotypes CIP- 396004.337 gave the highest mean tuber yield (25.66 t/ha), while CIP-395011.2 gave the lowest (17.78 t/ha). Combined ANOVA indicated that the main effect due to environments, genotypes and genotype by environment interaction were highly significant. The contribution of E, G and GEI to the total variation in tuber yield was about 47.11%, 8.83% and 44.07%, respectively. The GEI was further partitioned using GGE biplot model. The first two principal components obtained by singular value decomposition of the centered data of tuber yield explained 71.26% of the total variability caused by (G+GE). Out of these variations PC1 and PC2 accounted 51.24 and 20.02% variability, respectively. GGE biplot view of this study identified Serinka as ideal testing location and CIP- 396004.337 as ideal genotype for Amhara region in Ethiopia.